The presence of Aspergillus fumigatus in asthmatic airways is not clearly related to clinical disease severity. Issue 5 (31st October 2019) - Sullivan, Ashley; Hunt, Eoin B.; Ward, Chris; Lapthorne, Susan; Eustace, Joseph A.; Fanning, Liam J.; Plant, Barry J.; O'Byrne, Paul M.; MacSharry, John A.; Murphy, Desmond M.
Abstract: Background: It is suggested that airway fungi, in particular Aspergillus may impinge on clinical phenotype in asthma. Indeed, the term severe asthma with fungal sensitization (SAFS) has been coined. We aimed to ascertain whether the presence of fungi, in particular Aspergillus fumigatus, in the airway correlated with asthma severity and control. Furthermore, we aimed to determine whether traditional markers of Aspergillus sensitization related to the presence of Aspergillus within the airway. Methods: Sixty‐nine patients characterized by asthma severity (GINA) and level of control (ACQ‐7) underwent bronchoscopy and bronchoalveolar lavage (BAL). Serum was assessed for A fumigatus‐ specific IgE and total IgE. Galactomannan and relevant cytokine levels were assessed in serum, plasma and BAL. BAL was analyzed for the presence of A fumigatus. Results: In BAL, fungi were visible by microscopy in 70% and present by qPCR in 86% of patients, while A fumigatus was detectable by qPCR in 46%. Plasma and BAL IL‐4, IL‐6, IL‐10, IL‐13 and TNF‐α correlated with BAL fungal presence, while plasma IL‐17 correlated with BAL fungal presence. Aspergillus positive BAL correlated with increased plasma and BAL IL‐6 and BAL IL‐13. There was no relationship between fungal airway presence and steroid dose, asthma severity or control. The presence of Aspergillus within the airway did not relate to serum IgE positivity for Aspergillus . Conclusions: Fungi were present in a large proportion of our asthmatic patients' airways, but their presence was not predicted by traditional markers of sensitization, nor did it appear to be related to measures of disease severity or control. Abstract : In our cohort of asthmatic patients, fungus was observed directly by microscopy in 70% and by qPCR in 86%, while Aspergillus fumigatus was detectable by qPCR in 46%. The presence of fungus in BAL correlated with BAL IL‐4, IL‐6, IL‐10, IL‐13 and TNF‐α and with plasma levels of IL‐4, IL‐6, IL‐10, IL‐13, IL‐17 and TNF‐α. The presence of fungus or A fumigatus in the airway was not related to levels of asthma control or severity. Abbreviation: BAL, bronchoalveolar lavage